Where do we go from here? Reconciling implementation failure of PrEP for Black women in the South. Leveraging critical realism to identify unaddressed barriers as we move forward - Irie, Whitney C.; Mahone, Anais; Heffron, Renee; Elopre, Latesha (Frontiers in Reproductive Health, 2024)
IntroductionPrEP, a highly effective HIV prevention measure, provides autonomy to individuals in managing their HIV acquisition vulnerability. Despite its availability in tenofovir-based oral pills and injectable cabotegravir formulations, PrEP uptake among Black cisgender women in the U.S. South, a region with a high HIV burden, remains critically low. This demographic faces a disproportionately high rate of new HIV diagnoses, yet fewer than 10% of women in the US who could benefit from PrEP are currently receiving it.MethodsUtilizing a critical realism interpretative framework, this narrative review employed a tri-level analysis strategy to examine the empirical, actual, and real domains influencing PrEP implementation among Black women in the Southern U.S. The empirical level refers to observable events and data (e.g., PrEP uptake rates), the actual level encompasses experiences and actions that may not always be directly observed (e.g., healthcare interactions and community engagement), and the real level involves the deeper structures and mechanisms (e.g., systemic racism and cultural narratives) that shape these outcomes. A comprehensive search of peer-reviewed literature from PubMed and other sources was conducted to identify barriers and facilitators to PrEP uptake in this population.ResultsThe analysis revealed significant barriers, including structural violence, socioeconomic disparities, medical mistrust, stigma, and inadequate healthcare policies. Empirical data showed variability in PrEP awareness and interest among Black women, while actual experiences highlighted misaligned marketing strategies, financial constraints, and interpersonal dynamics. At the real level, underlying mechanisms such as systemic racism and cultural narratives were identified as critical impediments to PrEP uptake.DiscussionAddressing these multifaceted barriers requires a comprehensive, multi-level approach that integrates personalized, community-centric strategies. Emphasizing the need for healthcare providers, community leaders, researchers, and policymakers to collaborate, the review proposes actionable strategies to enhance PrEP implementation, focusing on education, structural reforms, and policy changes to improve access and acceptability among Black women in the South.